2018
DOI: 10.1039/c8sm01562g
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase equilibrium and the effect of a water-soluble polymer on the interaction between droplets in water-in-oil microemulsions

Abstract: Effects of additive PEG on the interaction enthalpy and entropy between droplets compete and result in decreases of Tc and stability of microemulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The test tubes were placed under 25°C for 1 h to determine the microemulsion particle size . [14,[22][23][24]…”
Section: Influence Of Food Additives On Protein Microemulsion Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The test tubes were placed under 25°C for 1 h to determine the microemulsion particle size . [14,[22][23][24]…”
Section: Influence Of Food Additives On Protein Microemulsion Stabilitymentioning
confidence: 99%
“…[11] The commonly used food-grade surfactants are soybean lecithin, Tween, span, and sucrose fatty acid ester . [12][13][14] Some studies have shown that the emulsifying effect on the stability of microemulsion of combined surfactant is better than that of a single surfactant, the stability of microemulsion is better. Short-and middle-chain alcohols, such as ethanol, glycerol, and n-butyl alcohol, are multi-selected as cosurfactants in microemulsions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation